Attributing snow cover extent changes over the Northern Hemisphere for the past 65 years. (1st June 2021) - Guo, Hui; Yang, Yuting; Zhang, Wenjie; Zhang, Cicheng; Sun, Hui
Abstract: Snow is a crucial component of the cryosphere and its has been experiencing a significant decline for the Northern Hemisphere (NH) (35–90°N) snow cover extent (SCE) in March-April over the 1948–2012 period. However, the causes of this historical snow cover decline are still uncertain. Here, based on the Global Land Data Assimilation System version 2.0 (GLDAS) reanalysis reanalyzed snow cover extent (SCE) and climate model simulations that separate different anthropogenic forcings, we attribute changes of spring SCE over the NH to anthropogenic and natural climate forcings using an optimal fingerprint technique. We find that fingerprints from greenhouse-gases (GHG) and stratospheric aerosols can be clearly detected in the historical SCE records, whereas natural forcing has not contributed to the long-term SCE trend in a discernible way. The GHG-induced warming is primarily responsible for the NH SCE decline, which, however, has been partly offset (by ∼16%) by aerosol-induced climatic cooling. Our findings confirm the negative effect of warming on SCE changes yet highlight the positive role of aerosols in slowing SCE decline over the past 65 years.